Effect of cavitation jet on the structural, emulsifying properties and rheological properties of soybean protein‐oxidised aggregates. (31st May 2022) - Guo, Yanan; Li, Bailiang; Cheng, Tianfu; Hu, Zhaodong; Liu, Shuangqi; Liu, Jun; Sun, Fuwei; Guo, Zengwang; Wang, Zhongjiang
Summary: The objective of this study was to investigate the effects of cavitation jets on the structural, emulsifying and rheological properties of soybean protein oxidation aggregates. The results showed that oxidation might induce the formation of larger particle sizes and molecular weight protein aggregates and the decrease of emulsifying properties. The cavitation jet at a short treatment time (<6 min) broke down the disulphide bonds and protein skeleton structures, which reduced the aggregate sizes and molecular weights and increased the emulsion activities, emulsion stabilities, apparent viscosity and elastic modulus. The cavitation jet at a long treatment time (>6 min) supported disulphide bond formation among molecules by intermolecular interactions to form protein aggregates. In addition, the skeleton structure showed cross‐linking aggregation. This increased the particle sizes and molecular weights and reduced the emulsion properties, consistency index K and elastic modulus. The findings showed that a cavitation jet at 6 min on oxidised aggregates of soybean protein might enhance the structural, emulsifying and rheological characteristics for the industry. Abstract : Cavitation jet at a short time could damage protein aggregates, increasing in emulsifying properties. While cavitation jet at a long treatment time could promote the formation of protein aggregates, resulting in decrease of emulsifying properties and elastic modulus.